The South African Arrhythmogenic Right Ventricular Cardiomyopathy Registry: A brief review and a status report - Hendricks, Neil; Mayosi, Bongani M.; Okreglicki, Andrzej (SA Heart Journal, 2017)
Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC), commonly an inherited condition affecting cell junctions, may present with sudden death or life-threatening arrhythmias. The pathogenesis, clinical presentation, diagnostic evaluation and treatment are reviewed. The South African ARVC Registry is described, giving the aims, organization and missions which include: establishment of a DNA/tissue bank, epidemiology, risk assessment and evaluation of therapy, imaging, pathological diagnosis and diagnostic validation. Results of analysis of the first 80 confirmed cases enrolled in the registry confirm its familial occurrence, high mortality and involvement of the left ventricle. A common finding is participation in sport. A new mutation has been discovered affecting the plakophyllin gene. Physicians are invited to refer patients with confirmed or suspected ARVC for inclusion in the Registry.